PENGARUH KOMPETENSI, INDEPENDENSI DAN PENGALAMAN AUDIT TERHADAP PENDETEKSIAN KECURANGAN DALAM LAPORAN KEUANGAN PEMERINTAH DAERAH PADA BADAN PEMERIKSA KEUANGAN PERWAKILAN PROVINSI NUSA TENGGARA TIMUR - Constantinus Nurak; Yohana Febiani Angi (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2022)
This research aims to determine the effect of competence, independence, and audit experience on fraud detection. This research was conducted on Badan Pemeriksa Keuangan (BPK) for the province of East Nusa Tenggara. The number of samples used in this research were 51 auditors. Data collection was carried out by questionnaire using simple random sampling method. The data analysis technique used is multiple linear regression analysis using the SPSS 25 application program. The result showed that the competence and audit experience have a significant impact on the fraud detection, while the independence variable do not have a significant impact on fraud detection. The result of the F test (simultaneous) showed that competence, independence and audit experience together have a significant impact on fraud detection. The coefficient of determination showed that competence, independence, and audit experience are able to explain the dependent variable (fraud detection) by 76,7%, while the remaining 23,3% is influenced by other variables outside the research.